Mining Knowledge TV: Uma Abordagem de Ambiente de KDD com Ênfase em Mineração de Dados no Ambiente da Knowledge TV - Patrício Júnior, José Carlos Almeida (2012)
The Interactive Digital TV brings many innovations to the existing analog scenario, such as improved sound quality, image, number of channels, programs and services available to the user. However, the information representing the structured multimedia content are presented in a traditional format of tables and files, not providing interoperability between the information, nor having semantics. This way, the project Knowledge TV - KTV proposes to organize the data in the DTV semantically, using this concept of Semantic Web and knowledge representation, and provides an architecture for application development. A major component of the KTV is the environment of knowledge discovery in databases supported by semantic concepts. This environment aims to discover useful knowledge in the data through data mining, semantically organize them and make them available as a service. In this context, this work aims to specify and develop this environment that this approach will be called the Mining Knowledge TV - MKTV.